2003
DOI: 10.1097/00129492-200311000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Head-Impulse and Caloric Tests in Patients With Dizziness

Abstract: The head impulse test, when used as a bedside test, and the caloric test are by no means redundant methods. The information obtained form both can be used in combination to obtain a better insight into the degree of vestibular dysfunction of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 11 publications
2
83
0
6
Order By: Relevance
“…It is known that the probability of a pathologic bHIT increases with UW and that a UW of 42.5% ensures a pathological bHIT [31,42]. Our data support this finding also for the vHIT.…”
Section: Differences Between CI and Vhitsupporting
confidence: 87%
“…It is known that the probability of a pathologic bHIT increases with UW and that a UW of 42.5% ensures a pathological bHIT [31,42]. Our data support this finding also for the vHIT.…”
Section: Differences Between CI and Vhitsupporting
confidence: 87%
“…According to the results reported by Perez and Rama-Lopez (26), 100% specificity seems to be impossible to achieve. These authors found that 9.5% to 19% of the 265 acute dizziness patients tested by them either had only an abnormal caloric test result or only an abnormal HIT result (26). This may be explained in that each of the 2 tests investigates different frequency ranges: caloric testing has its dominant frequency at 0.0025 Hz, whereas that for HIT is 4 to 5 Hz.…”
Section: Head Impulse Testmentioning
confidence: 99%
“…The signs and symptoms must be described precisely, and the study design must comply with accepted methodologic criteria. Newman-Toker et al 40 Cnyrim et al 28 Perez et al 42 Beynon et al 23 Harvey et al 34 Harvey et al 33 0. …”
Section: Discussionmentioning
confidence: 99%